Let Go of Your Hands - Cheuk, Jennifer (Auckland University of Technology, 2023)
This thesis consists of practice-led research in the form of a full-length script for a feature film; plus a 10,000-word essay (exegesis). A summary of the script is as follows: Let Go Of Your Hands is a coming-of-age film centred on the family and sibling dynamics of a mixed-race, Chinese-Pakeha household in present day Aotearoa. Siblings, Katie and David Leung are forced to reconcile with their identity and culture before Katie leaves the country for a prestigious opportunity. But little does the family know that Katie is desperate to find a way out of this opportunity, and David is secretly dealing with his wife’s pregnancy – leading the siblings to question their connection to their culture, language, parents, and each other. The script is framed by an Exegesis which is a 10,000-word essay on the subject of: (a) the genre of the script (b) the development process from synopsis to second draft